How to quantify qualitative characteristics of societal differences: a method for systematic comparison of qualitative data (SCQual). Issue 3 (4th May 2022) - Frericks, Patricia
ABSTRACT: Social research is rich in methods for analysing societal differences. Yet, although qualitative characteristics are a key component to understanding such differences, the analysis of qualitative data remains a major methodological challenge in most social research, particularly when aiming to compare more than a few cases. The article proposes an innovative method for systematic comparison of qualitative data (SCQual), applying Weber's original idea of ideal types as a tool to measure and compare societal differences. This method allows for the quantification of qualitative data, thereby enabling systematic analysis and repeatable comparison of the qualitative characteristics of societal differences for a relatively large number of cases. Developed for the comparative analysis of essential characteristics of social orders, particularly comparative welfare state analysis, SCQual may also be applicable to other areas of social research.